2018
DOI: 10.1016/j.placenta.2018.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress induces senescence and sterile inflammation in murine amniotic cavity

Abstract: OS induction by cigarette smoke extract cause fetal tissue protein damage, p38MAPK activation, senescence and sterile inflammation in the amniotic cavity of mouse. Prevention of p38MAPK activation can be a novel approach to prevention of adverse pregnancy outcomes related to OS induced premature senescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 28 publications
3
46
0
Order By: Relevance
“…Similar to our in vitro studies, our laboratory has also reported that OS can cause p38MAPK activation and senescence in the amniotic cavity of CD‐1 mice . OS‐induced p38MAPK activation, senescence, sterile inflammation, and pre‐term labor were inhibited by pharmacologic p38MAPK inhibitor SB203580 and antioxidant N‐acetyl cysteine, supporting the hypothesis that the senescence pathway is functionally active in this model .…”
Section: Introductionsupporting
confidence: 87%
See 3 more Smart Citations
“…Similar to our in vitro studies, our laboratory has also reported that OS can cause p38MAPK activation and senescence in the amniotic cavity of CD‐1 mice . OS‐induced p38MAPK activation, senescence, sterile inflammation, and pre‐term labor were inhibited by pharmacologic p38MAPK inhibitor SB203580 and antioxidant N‐acetyl cysteine, supporting the hypothesis that the senescence pathway is functionally active in this model .…”
Section: Introductionsupporting
confidence: 87%
“…OS‐induced p38MAPK activation, senescence, sterile inflammation, and pre‐term labor were inhibited by pharmacologic p38MAPK inhibitor SB203580 and antioxidant N‐acetyl cysteine, supporting the hypothesis that the senescence pathway is functionally active in this model . Senescence‐associated sterile inflammation in these mice contributes to the initiation of labor . We hypothesize that GSK3β and p38MAPK activities are balanced to maintain cellular homeostasis during gestation, but OS at term causes overwhelming p38MAPK activation to suppress GSK3β's function, resulting in senescence.…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…Increased OS at term has been shown to induce laborassociated changes, such as cellular senescence, matrix metallopeptidase 9 up-regulation, and increased proinflammatory cytokine production in fetal membrane cells, including AECs and AMCs (2,23). CSE, a potent and reliable OS inducer (2,17,23,(31)(32)(33)(34)(35), has been shown to recreate the labor phenotype (OS experienced at term labor in amnion membranes) in vitro and to induce a static state of EMT in AECs (17,33). EMT contributes to sustained inflammation that promotes the labor-related cascade of events.…”
Section: Os Induces Changes In Amnion Intermediate Filament Expressiomentioning
confidence: 99%